Factores de riesgo asociados a la disminución de la agudeza visual en niños de la escuela “Dr. Reinaldo Espinoza Aguilar” - Álvarez Jiménez, Karen Esthefanía (2023)
Visual impairment is a social problem affecting millions of children around the world. The lack of detection of its causes has been an economic and social burden, mainly in developing countries. Some risk factors interact to increase the susceptibility to decreased visual acuity and its progression, which is crucial to identify during childhood. In this context, the research takes place to know the risk factors associated with decreased visual acuity, which will contribute to finding out which are the most prevalent in our environment, establishing as the main objective to determine the risk factors associated with decreased visual acuity in children. It was a descriptive cross-sectional study with about 108 children from the first to the seventh grades of an elementary school in the Dr. Reinaldo Espinoza Aguilar school, using a data collection form with questions aimed to identify risk factors and the Snellen chart with which measure visual acuity. The results of the research showed that of the 108 children, the majority were males between 5 and 12 years of age, 13% of whom presented diminished visual acuity between mild and moderate, and the main risk factors were identified as the history of a family member who wears glasses in a percentage of 64% and asthenopic factors in 36%. It concluded that in the population studied, 14 children presented decreased visual acuity, and the risk factors identified were a history of a family member wearing glasses followed by asthenopic factors